Evaluation of Sustainable Structural Concrete Using Recycled Aggregate and Aramid Fiber Sheet. (14th December 2016) - Cho, Y. S.; Jang, H. S.; Back, S. K.; Choi, M. I.; Hong, S. U.; Lee, Y. T.
Abstract : The purpose of this study was to evaluate the flexural performance of recycled aggregate RC beam reinforced with aramid fiber sheets. Compressive strength of concrete using recycled aggregate is generally similar or slightly lower than normal concrete. To improve the compressive strength, aramid fiber sheets have been used in this study. This study examines the structural behavior of concrete beams prepared with recycled aggregate and strengthened aramid fiber sheets at varying locations. One concrete beam as a control specimen, that is prepared with 30 percent recycled aggregate and 70 percent natural aggregate, has been tested, and 3 more strengthened beams (bottom, bottom and sides, bottom and both ends with U-shaped strengthened beams) are tested. The ultimate loads have increased by 38.01%, 39.88%, and 100.79% for bottom, bottom and sides, bottom and both ends with U-shaped strengthened beams. The ductility ratios are 2.75~6.20 for strengthened beams. The experimental results showed that the strengthening system with U-shaped band controls the premature debonding and provides a more ductile failure mode than the strengthening system without U-shaped bands. It can be found that the ultimate strength of H40-RGA30-BS specimen based on load-deflection curves shows most promising result. The experimental results are compared with the analytical results of nonlinear flexural behaviors for strengthened reinforced recycled aggregate concrete beam.